Flow distribution in an unsymmetrical compound channel. Issue 1 (2nd January 2018) - Devi, K.; Khatua, K. K.
Abstract: Flow modeling in rivers during flood is a complex matter as two-phase geometry occurs normally called as compound channels. Rivers with two equal adjoining flood plains are referred to as symmetric otherwise, they are known as unsymmetrical compound channels. The interaction technique at shear layer induces complex flow phenomenon, indeed due to the higher velocity in the main channel than the flood plain. Present work focuses on predicting the flow and its distribution in an unsymmetrical compound channel as it emulates a natural river. The hydraulic resistance of an unsymmetrical compound channel is attributed by sub-sectional geometry, boundary roughness and flow characteristics. As channel conveyance is influenced by boundary friction along the periphery of the compound channel which manifests the resistance to flow. So, two improved expressions are proposed depending on geometric, roughness and hydraulic parameters to predict boundary shear distribution in each sub-compartments. Further, the apparent shear at the junction is quantified in terms of apparent shear stress ratio. The current study is analyzed through experimental and natural river data-sets for quantifying the magnitude of momentum transfer at both the vertical interfaces. Moreover, this approach is implemented successfully for computing individual floodplain discharge in such channels.